Infusion of Human Bone Marrow-Derived Mesenchymal Stem Cells Alleviates Autoimmune Nephritis in a Lupus Model by Suppressing Follicular Helper T-Cell Development. Issue 1 (January 2016) - Jang, Eunkyeong; Jeong, Mini; Kim, Sukhyung; Jang, Kiseok; Kang, Bo-Kyeong; Lee, Dong Yun; Bae, Sang-Cheol; Kim, Kyung Suk; Youn, Jeehee
Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by the production of autoantibodies to components of the cell nucleus. These autoantibodies are predominantly produced with the help of follicular/helper T (Tfh) cells and form immune complexes that trigger widespread inflammatory damage, including nephritis. In recent studies, mesenchymal stem cells (MSCs) elicited diverse, even opposing, effects in experimental and clinical SLE. Here we investigated the effect of human bone marrow-derived MSCs (hBM-MSCs) in a murine model of SLE, the F1 hybrid between New Zealand Black and New Zealand White strains (NZB/W). We found that infusion of female NZB/W mice with hBM-MSCs attenuated glomerulonephritis; it also decreased levels of autoantibodies and the incidence of proteinuria and improved survival. These effects coincided with a decrease in Tfh cells and downstream components. Infiltration of long-lived plasma cells into the inflamed kidney was also reduced in the hBM-MSC-treated mice. Importantly, hBM-MSCs directly suppressed the in vitro differentiation of naive CD4+ T cells toward Tfh cells in a contact-dependent manner. These results suggest that MSCs attenuate lupus nephritis by suppressing the development of Tfh cells and the subsequent activation of humoral immune components. They thus reveal a novel mechanism by which MSCs regulate humoral autoimmune diseases such as SLE.